EVALUASI TUGAS CAMAT DALAM MEMBINA PENYELENGGARAAN PEMERINTAHAN DESA DI KECAMATAN ROKAN IV KOTO KABUPATEN ROKAN HULU - Syafhendry Syafhendry; Delpi Susanti (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2018)
study aims to determine and explain the results of the implementation of the authority of the Camat in fostering the Implementation of Village Government in Rokan IV Koto Sub-District Rokan Hulu and to know the factors inhibiting the tasks of the sub-district Head in fostering the Village Government, and to know the appropriate pattern of coaching for the implementation of the village government in Rokan IV Koto Subdistrict, this research is in the form of field research by way of survey with Likert-scale processing, while viewed from the nature of this research is descriptive analysis that explains and develops various research findings in the field and analyze the data so that obtained an answer to the problems formulated, the population is mostly and some are small, so the researchers do the sampling. For the Village Head is directly limited to 3 Villages with 3 Village Heads, Village Secretaries with 3 Sekdes, Village Governors 3, Dusun Head 3, and BPD 19 using techniques using saturated sampling techniques other term census techniques. To analyze the data, in this case the data that have been collected are grouped according to each data type then presented in Likert scale table. Furthermore, the data that has been presented in the form of the table is analyzed descriptively, ie analysis in the form of descriptions and explanations of the table presented, from the results of the discussion that has been done it can be drawn conclusions, among others are: Evaluation of District Camat in Fostering the Implementation of Village Government in Rokan IV Koto Sub-district Rokan Hulu District with 6 indicators of assessment are: Efficiency, Effectiveness, Responsiveness, Supervision, Consultation of Government Affairs Implementation, it can be categorized as Good Enough. Based on observation items obstacles observation faced in the implementation of village administration is the budget for the implementation of these activities so that the element of the builder is a major element that must be improved prior to coaching on the specially developed in Rokan IV Koto District Rokan Hulu District.